Integrated phylogenomic analyses unveil reticulate evolution in Parthenocissus (Vitaceae), highlighting speciation dynamics in the Himalayan–Hengduan Mountains. Issue 2 (3rd December 2022) - Yu, Jinren; Niu, Yanting; You, Yichen; Cox, Cymon J.; Barrett, Russell L.; Trias‐Blasi, Anna; Guo, Jing; Wen, Jun; Lu, Limin; Chen, Zhiduan
Summary: Hybridization caused by frequent environmental changes can lead both to species diversification (speciation) and to speciation reversal (despeciation), but the latter has rarely been demonstrated. Parthenocissus, a genus with its trifoliolate lineage in the Himalayan–Hengduan Mountains (HHM) region showing perplexing phylogenetic relationships, provides an opportunity for investigating speciation dynamics based on integrated evidence. We investigated phylogenetic discordance and reticulate evolution in Parthenocissus based on rigorous analyses of plastome and transcriptome data. We focused on reticulations in the trifoliolate lineage in the HHM region using a population‐level genome resequencing dataset, incorporating evidence from morphology, distribution, and elevation. Comprehensive analyses confirmed multiple introgressions within Parthenocissus in a robust temporal–spatial framework. Around the HHM region, at least three hybridization hot spots were identified, one of which showed evidence of ongoing speciation reversal. We present a solid case study using an integrative methodological approach to investigate reticulate evolutionary history and its underlying mechanisms in plants. It demonstrates an example of speciation reversal through frequent hybridizations in the HHM region, which provides new perspectives on speciation dynamics in mountainous areas with strong topographic and environmental heterogeneity.